ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. MANDOM Tbk TAHUN 2016-2020 - Wulan Damayanti; Ari Nurul Fatimah (Jurnal Akuntansi dan Keuangan (JAK), 2021)
This study analyzes the financial performance of PT Mandom Tbk. This study aims to determine how the financial performance of PT Mandom Tbk during the 2015 - 2020 reporting year. The data and information used in this study were obtained from the Indonesia Stock Exchange. The test is carried out based on four categories of financial ratios, namely, Profitability Ratios, Liquidity Ratios, Solvency Ratios, and Activity Ratios. The study was conducted using a descriptive quantitative approach and the data is secondary data in the form of financial statements of income and statements of financial position obtained from the Indonesia Stock Exchange (IDX). Based on the results of research analysis using the profitability ratios of the company's financial performance, the condition is not good. Based on the liquidity ratio analysis, the company's financial performance shows a good condition. Based on the analysis of the solvency ratio, the company's financial performance shows a good condition. Based on the activity ratio analysis of the company's financial performance, it shows good conditions for receivable activities and not good for inventory activities and fixed asset activities.